2021
DOI: 10.1002/ejoc.202100293
|View full text |Cite
|
Sign up to set email alerts
|

Electrosynthesis of Stable Betulin‐Derived Nitrile Oxides and their Application in Synthesis of Cytostatic Lupane‐Type Triterpenoid‐Isoxazole Conjugates

Abstract: Novel lupane‐type triterpenoid‐isoxazole conjugates were designed by direct placing of isoxazole linker at C(17) of triterpenoid. The suggested synthetic sequence demonstrates successful combination of electro‐organic synthesis and conventional approaches. TEMPO‐mediated electrooxidation of betulin to betulinal was developed and optimized at boron‐doped diamond anodes with potassium acetate as inexpensive supporting electrolyte. Betulinal‐derived oxime was further selectively electro‐oxidized at a graphite ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 142 publications
(100 reference statements)
0
12
0
4
Order By: Relevance
“…Compound 21d ( Figure 14 ) was found on cells of breast cancer MCF7 (12.49 ± 1.18 µM) and lung cancer A549 (13.15 ± 1.56 µM). The constitutive relationship indicated that compounds with hydrophilic substituents on the isoxazole ring had stronger cytotoxic activity [ 47 ].…”
Section: Biological Effects Of Natural Products Containing the Isoxaz...mentioning
confidence: 99%
“…Compound 21d ( Figure 14 ) was found on cells of breast cancer MCF7 (12.49 ± 1.18 µM) and lung cancer A549 (13.15 ± 1.56 µM). The constitutive relationship indicated that compounds with hydrophilic substituents on the isoxazole ring had stronger cytotoxic activity [ 47 ].…”
Section: Biological Effects Of Natural Products Containing the Isoxaz...mentioning
confidence: 99%
“…The SAR study proved that the substituents attached to the isoxazole ring significantly influenced the overall cytotoxic effects; as an example, the saponin-like derivatives containing glucose substituents grafted on the isoxazole fragment induced cytotoxic effects against A549 and MCF7 cell lines, but no activity was recorded in the HepG2 cells. The most promising results were reported for derivatives bearing small hydrophilic substituents on the isoxazole ring, such as hydroxymethyl (Bet 9–10), 2-hydroxypropan-2-yl (Bet 11), (2-hydroxyethoxy)methyl (Bet 12), carboxyl (Bet 13), and (acetylthio)methyl (Bet-14), for which IC 50 values within the micromolar range were calculated; moreover, the selected compounds proved to be harmless against healthy human fibroblasts [ 32 ].…”
Section: Betulinmentioning
confidence: 99%
“…In general, the presented approach is analogous to the synthesis of isoxazoles, and isoxazolines from aldoximes [29] . The synthesis of nitriles, isoxazolines and isoxazoles can be achieved by electrolysis via nitrile oxides as key intermediates [30–34] . These reactions have been investigated since the late 1980s when Shono et al.…”
Section: Introductionmentioning
confidence: 99%